Вы находитесь на странице: 1из 3

# 9/3/2018 Laplace Transform of Intergrals | Advance Engineering Mathematics Review

MATHalino
Engineering Mathematics

CE Math

## Laplace Transform of Intergrals

Theorem
If L {f (t)} = F (s) , then

t
F (s)
L [∫ f (u) du] =
0
s

Proof
t

## Let g(t) = ∫ f (u) du

0

then, ′
g (t) = f (t) and g(0) = 0

## Taking the Laplace transform of both sides,

L {g (t)} = L {f (t)}

## From Laplace transform of derivative, ′

L {g (t)} = s L {g(t)} − g(0) and from the Theorem above,
L {f (t)} = F (s)

Thus,
s L {g(t)} − g(0) = F (s)

s L {g(t)} − 0 = F (s)

s L {g(t)} = F (s)

F (s)
L {g(t)} =
s
t
F (s)
L [∫ f (u) du] =
0
s

## Tags: Laplace proof Laplace transform transform of integral

9/3/2018 Laplace Transform of Intergrals | Advance Engineering Mathematics Review

## Problem 01 | Laplace Transform of Intergrals

Problem 02 | Laplace Transform of Intergrals
Problem 03 | Laplace Transform of Intergrals
Evaluation of Integrals

## ‹ Problem 04 | Laplace Transform of up Problem 01 | Laplace Transform of

Derivatives Intergrals ›

Subscribe to MATHalino.com on

## Custom Search Search

9/3/2018 Laplace Transform of Intergrals | Advance Engineering Mathematics Review

Infinite Series
Laplace Transform
Laplace Transform by Direct Integration
Table of Laplace Transforms of Elementary Functions
Linearity Property | Laplace Transform
First Shifting Property | Laplace Transform
Second Shifting Property | Laplace Transform
Change of Scale Property | Laplace Transform
Multiplication by Power of t | Laplace Transform
Division by t | Laplace Transform
Laplace Transform of Derivatives
Laplace Transform of Intergrals
Problem 01 | Laplace Transform of Intergrals
Problem 02 | Laplace Transform of Intergrals
Problem 03 | Laplace Transform of Intergrals
Evaluation of Integrals